Prevalence of Diarrhea in the Community in Bagan Dalam Village, Tanjung Tiram District - Sheillawany, Anggun; Oesraini, Daffa Diba; Saragih, Devi Herdini; Wulandari, Nabila; Prasetyo, Angga Dwi; Utami, Tri Niswati (Jurnal Keperawatan Priority, 2025)
Diarrhea is one of the most prevalent health problems in Indonesia, especially in areas with limited access to clean water and adequate sanitation facilities. In addition, diarrhea is one of the leading causes of death in the world, especially in children under 5 years of age, with approximately 2.2 million deaths each year. The purpose of this study was to increase community knowledge about diarrhea in Bagan Dalam Village, Tanjung Tiram Sub-District, Batu Bara Regency to prevent diarrhea. The research method used is quantitative with a pre-experimental approach designed in the form of one-group pre-test and post-test. Sampling using the accidental sampling formula obtained 30 samples in this study. This research instrument uses a questionnaire with data analysis techniques using paired simple t-test. Based on the results of the pre-test and post-test tests, there was no significant difference in knowledge between before and after counseling, with an average value of 0.833. This is because the education was only conducted once, so the impact on changes in the level of knowledge of the community who became the research sample was not large.